Compute the derivative of the given function in two different ways.
\displaystyle{ h(x) = \frac{{x^{3}+3x^{2}}}{{2x^{2}}}
}

- Use the Quotient Rule,
\displaystyle\left[\frac{f}{g}\right]' = \frac{g\cdot f' - f \cdot g'}{g^2} . (Fill in each blank, then simplify.)\(h'(x) = \)\(\Big(\)\( \Big) \cdot \Big(\) \(\Big) - \Big(\) \(\Big) \cdot \Big(\) \(\Big)\) \( = \) - Use algebra first to simplify
h , then differentiate without the Quotient Rule.h'(x) =

You can earn partial credit on this problem.